Hubungan Paparan Informasi dengan Tingkat Kecemasan Pada Ibu Hamil - Agustini, Ni Komang Tri; Sagitarini, Putu Noviana; Wahyuningsih, Luh Gde Nita Sri (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
Anxiety is a common experience during pregnancy and can have significant implications for both the mother's health and the developing fetus. One factor that can contribute to maternal anxiety is exposure to information. The vast amount of information available to pregnant women through various sources, such as books, websites, and social media, can be overwhelming and confusing. Furthermore, the quality and accuracy of information available online can vary widely. This can make it difficult for pregnant women to determine which sources are reliable and trustworthy. As a result, they may become overwhelmed with doubt and uncertainty, leading to increased anxiety. The purpose of the study was to determine the relationship between exposure to information and the level of anxiety of pregnant women. The study used a descriptive cross-sectional correlation design using the Pregnancy Anxiety Questionnaire-Revised for All Pregnant Women Regardless of Parity (PRAQ-R2). The sample used 80 respondents using consecutive sampling technique. Data analysis using Chi Square test. The results showed that information exposure including exposure to information (p=0.01), confidence in information (p=0.009), and information support (0.021) were associated with the level of anxiety of pregnant women. This study highlights the importance of providing clear, accurate, and supportive information to pregnant women to help reduce anxiety and promote positive mental health outcomes.